A DESCRIPTIVE STUDY ON THE SATISFACTION OF LOYALTY PROGRAMS AND REPEAT PURCHASE BEHAVIOUR OF SOUTH AFRICAN YOUTH - Ramathlape, Rebaone (The IIE, 2022)
A heightened level of loyalty program awareness, with regards to customer satisfaction, has led to greater repeat purchase behaviour. The objective hereof is to determine and describe the factors that influence customer satisfaction and repeat purchase intention towards loyalty programs. What is unknown to the nature of and the influence of loyalty programs on the repeat purchase behaviour of South African youth? (Dlamini and Chinje, 2019). In line with this, the research study aims to unpack the factors that impact and influence loyalty programs satisfaction and repeat purchase behaviour, through following a positivistic research approach. This research study is of a quantitative, cross-sectional, nature. The Theory of Planned Behaviour determined the foundation from which this study was conducted, as perceived behavioural control is a key factor hereof, focusing mainly on self-efficacy. The reviewed literature conceded factors related to customer satisfaction, loyalty programs and repeat purchase behaviour. The research study followed a positivistic approach, thus quantitative data was evaluated by means of particularly grouping statistical findings. The purpose of the research study was to measure the extent to which towards customer satisfaction of loyalty programs influences the repeat purchase behaviour of South African youth. From a sample of 23 responses, a seemingly positive customer satisfaction and repeat purchase behaviour towards loyalty programs was demonstrated. This study contributes to understanding perceived behavioural control factors, in relation to the customer satisfaction, influencing repeat purchase behaviour of loyalty programs.
Keywords: Buying patterns; Customer behaviour